CHECKLIST OF INDIAN FAIRYFLY (HYMENOPTERA: MYMARIDAE) PARASITOIDS: AN UPDATE - ATHITHYA, A.; MANICKAVASAGAM, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Fairyflies are internal, egg parasitoids (except two species) of agriculturally important insect pests belonging to Cicadellidae and Delphacidae. The checklist of Indian Mymaridae is updated by including two genera 31 new species, first report of 18 species from India, synonymization of five species and misidentification of seven species. As of now, the Indian mymarid fauna is known by 232 species under 39 genera. In addition, details of their distribution in India and also the places where the types are deposited are included in the checklist.